Your second act ebook Inspiring stories of reinvention. - Heaton, Patricia (2020)
An entertaining book "filled with inspirational anecdotes" ( People ) about second acts in life and reinventing yourself from beloved television actress Patricia Heaton—Emmy Award–winning star of Everybody Love's Raymond , The Middle , Patricia Heaton Parties , and most recently, Carol's Second Act . Patricia Heaton is one of TV's most recognizable and beloved moms. She's won three Emmys, two for her starring role as Debra Barone on the long-running comedy Everybody Loves Raymond , and followed that career-making role with another gem as Frances Heck on the popular sitcom The Middle . She returned to television as the lead in the series Carol's Second Act , which followed divorced fifty-year-old Carol Kenney (played by Heaton), who after raising two children and retiring as a teacher decides to finally pursue her dream of becoming a doctor. Patricia Heaton knows what it's like to stage a second act and navigate pivotal transitions in life. When Heaton's children left the nest, she found herself in a new and unfamiliar stage of life, compelling her to evaluate which direction to take next. Heaton discovered she had the time pursue passions that were previously placed on hold, both personally and professionally. She made her move and took a step forward in her career and for the first time, Heaton was not only the star of her own show, but also the executive producer. She now finds her greatest fulfillment in using her influence to support humanitarian efforts as a Celebrity Ambassador for World Vision, the world's largest non-governmental organization. She and her husband support their work in poverty relief around the globe, something that was planted in her heart long ago. Through her own experience, Heaton became curious about other people's stories of second-act transitions and ways to offer support in the process. Now, in Your Second Act , she shares wisdom from her own personal journey as well as insight from stories of numerous people across the country. From work to health, to love and more, the results are heartwarming, inspiring, and surprisingly relatable. "If you've been wanting to start your second act, Patricia Heaton may have just what you need" ( Today ). Filled with light-hearted anecdotes and pragmatic steps, Heaton shows us that midlife doesn't have to be about crisis when you focus on the opportunity. After all, it's never too late, or too early to stage your second act.